Natural Killer Cell Memory: Progress and Implications - Peng, Hui; Tian, Zhigang (Frontiers in Immunology, 2017)
Immunological memory is a cardinal feature of adaptive immunity. Although natural killer (NK) cells have long been considered short-lived innate lymphocytes that respond rapidly to transformed and virus-infected cells without prior sensitization, accumulating evidence has recently shown that NK cells develop long-lasting and antigen-specific memory to haptens and viruses. Additionally, cytokine stimulation alone can induce memory-like NK cells with longevity and functional competence, leading to emerging interest in harnessing NK cell memory for cancer immunotherapy. Here, we review the evidence of NK cell memory in different settings, summarize recent advances in mechanisms driving the formation of NK cell memory, and discuss the therapeutic potential of NK cells with memory-like properties in the clinical setting.